Gas barrier behavior of polyimide films filled with synthetic chrysotile nanotubes. Issue 15 (5th June 2013) - Wu, Yingji; Yudin, Vladimir E.; Otaigbe, Joshua U.; Korytkova, Elena N.; Nazarenko, Sergei
ABSTRACT Chrysotile nanotubes (ChNTs) were synthesized under hydrothermal conditions. These synthetic nanotubes crystallographically and morphologically mimic the nanofibrils of natural white asbestos but they are considerably shorter. ChNTs containing polyimide nanocomposites were prepared by a solution mixing/casting method. Oxygen and water vapor barrier of the nanocomposite films were tested and related to the amount, dispersion, and orientation of the nanotubes. The dispersion and orientation of the nanotubes were examined by transmission electron microscopy (TEM). The nanotubes were nanodispersed and oriented in the plane of the film in the nanocomposites with up to 4.5% (vol/vol) of ChNTs leading to a gradual increase of the gas barrier. The lowest gas permeability was 60% smaller than that for the pristine polyimide film. However, with the onset of nanotube micro aggregation at larger ChNTs loadings the nanotube dispersion and orientation were compromised and oxygen barrier was reduced. The efficacy of nanotubes to enhance polymer gas barrier was discussed and compared with that by nanoplatelets. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1184–1193